Evaluation of a current avian environmental toxicity guideline prescribed for pesticide evaluation for the prediction of the toxic effect of diclofenac in vultures - Naidoo, Vinny (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.